CHALLENGES IN BUILDING WRITTEN AND SPOKEN COMPARABLE CORPORA IN CORPUS LINGUISTICS - Turakulova, Dilafruz Muxammadsoli qizi (INTERNATIONAL CONFERENCES, 2023)
This article covers challenges while creating written and spoken comparable corpora. Moreover, it suggests possible solutions to some problems on the creation and use of various linguistic corpora.